Stroke Risk Prediction using Winsorizing Interquartile Range and Tree-Based Classification with Explainable Artificial Intelligence - Rahmadani, Fitria; Wiharto, Wiharto; Zuhdi, Shaifudin (Informatika, Universitas Jenderal Soedirman, 2025)
According to the Global Burden of Disease (GBD) Study, stroke is the third leading cause of death globally. Recognizing its signs early is crucial for both prevention and effective treatment. Although machine learning has made significant progress in predicting strokes, many current models operate like